The Impact of Emotional and Rational Thinking on Two Types of Speciesism - Broncel, Alicja; Trojan, Maciej; Bojarski, Szymon; Sikorska, Julia (Przegląd Psychologiczny, 2025)
Aim: In this study, we examined whether the mode of information processing and emotions influence the level of anthropocentric speciesism (the tendency to prioritize humans over other species) and pet speciesism (the tendency to prioritize companion animals over other species). Method: Participants (N = 499), randomly assigned to one of three conditions, resolved seven moral dilemmas and assessed the moral status, likability, intelligence and capacity to feel pain, of the included species (dog, bear, fish, and rat). Results: Individuals guided by emotions (vs. logic) demonstrated higher levels of pet speciesism. We did not observe the reverse relationship for anthropocentric speciesism. Emotions experienced towards species were relevant only for pet speciesism under emotional thinking conditions. Conclusion: The study only partially confirmed the results described in the literature. We suggest employing more objective manipulation methods in further research on speciesism.